Knife-edge and saddleback: Augustine & William James on the Psychology of the specious present - Hannan, Sean (My University, 2019)
In the late nineteenth century, William James raised the possibility that an ill-defined notion of ‘the present time’ might cause problems for future psychologists. This line of inquiry ultimately took James in a sanguine direction, as he convinced himself and many others that, even if our notion of the now remains fuzzy, we should proceed on the basis of whatever vague sense of the present seems appropriate for our clinical or experimental purposes. Almost fifteen hundred years before James, this same question of a specious present was asked by the Christian author Augustine of Hippo as part of an introspective interrogation of time in his Confessions. Augustine’s findings were less sanguine. The present, it turns out, is hard for us to define because it has no proper definition. In other words: the ‘now’ is not natural to time. And if that is the case, then time-bound animals like human beings would also be subject to a time without present. To try to describe the human psyche and diagnose its maladies while relying upon the idea of a specious present could cause us to mis-describe and misdiagnose the very phenomena we seek to explain or even heal. We thus find Augustine and James at odds over the specious present. In order to adjudicate their dispute, we should proceed by sketching out James’ psychological remarks and then positioning Augustine’s philosophical account against James. Once that has been done, we can try to nod in the direction of a way forward by introducing a third perspective, here tentatively termed ‘phenomenological,’ but originally rooted in the empirical psychology of James’ contemporary from the continent: Franz Brentano.
Keywords: William James; Augustine of Hippo; specious present; Franz Brentano; empirical psychology; stream of consciousness; nineteenth-century psychologist; saddleback hypothesis; current mental state; protention